2015
DOI: 10.21101/cejph.a4105
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition Changes in Adult Females after Lifestyle Intervention Are Influenced by the NYD-SP18 Variant

Abstract: Overweight/obese female carriers of the NYD-SP18 rs6971091 GG genotype exhibited a more beneficial response to the intensive lifestyle intervention than others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…More recently, the association has been detected in males, but not in females, in the Czech post-MONICA study [ 7 ]. The possible role of the NYD-SP18 in the determination of BMI has been further suggested in a small intervention study [ 8 ] of overweight non-diabetic females; the results suggest that common homozygotes profit more from the intensive life style intervention than carriers of the minor A allele.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the association has been detected in males, but not in females, in the Czech post-MONICA study [ 7 ]. The possible role of the NYD-SP18 in the determination of BMI has been further suggested in a small intervention study [ 8 ] of overweight non-diabetic females; the results suggest that common homozygotes profit more from the intensive life style intervention than carriers of the minor A allele.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the additive effect between this SNP and 1st intron polymorphism of the FTO gene on BMI values has been detected [ 7 ]. Finally, a small intervention study in females suggested that NYD-SP18 polymorphism could be a significant predictor of positive body composition changes after a short-term intensive life style intervention [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The program was based on supervised ten-week lifestyle modification interventions. [18][19][20] Dietary intervention involved adjusting energy intake to the age-related optimum (max. 7500 kJ/day).…”
Section: Interventionmentioning
confidence: 99%